Effect of molybdenum on productivity of clusterbean [Cyamopsis tetragonoloba (L.) Taub] varieties - Yadav, Arti; Yadav, L.R.; Yadav, S.S.; Verma, H.P.; Yadav, Neelam (Annals of Agricultural Research, 2018)
A field experiment was conducted at Agronomy farm, S.K.N. College of Agriculture, Jobner (Rajasthan) during kharif, 2015 on loamy sand soil. There were twenty treatment combinations consisting of five clusterbean varieties (RGC-936, RGC-1017, RGC-1033, RGC-1002 and RGC-197) and four levels of molybdenum (control, 0.5, 1.0 and 1.5 kg Mo/ha) tested in randomized block design with three replications. Results revealed that variety RGC-1033 proved significantly superior to RGC- 936, RGC-1017, RGC-1002 and RGC-197 in respect of dry matter accumulation, growth indices like CGR, RGR and LAI, pods/plant, seeds/pod and test weight. Similarly, the seed yield (1862 kg/ha), stover yield (3821 kg/ha) and biological yields (5683 kg/ha) were also significantly higher with variety RGC-1033. Result showed that molybdenum application at 1.0 kg/ha significantly increased yield attributes of clusterbean (number of pods/plant, number of seeds/pod, test weight) and seed, stover and biological yields. The per cent increase in seed yield with 1.0 kg Mo/ha was 22.1 and 8.0, respectively, over control and 0.5 kg Mo/ha. However, application of 1.5 kg Mo/ha remained at par with 1.0 kg Mo/ha. Soil application of molybdenum at 1.0 kg/ha gave higher net returns (Rs. 44813/ha) with higher B:C ratio (2.85) over control and 0.5 kg Mo/ha which was at par with 1.5 kg Mo/ha (Rs. 42288/ha).